Role of sphingolipid metabolism signaling in a novel mouse model of renal osteodystrophy based on transcriptomic approach - Yujia Wang; Yan Di; Yongqi Li; Jing Lu; Bofan Ji; Yuxia Zhang; Zhiqing Chen; Sijie Chen; Bicheng Liu; Rining Tang; Yuanyuan Ji (Chinese Medical Journal)
Abstract. Background:. Renal osteodystrophy (ROD) is a skeletal pathology associated with chronic kidney disease-mineral and bone disorder (CKD-MBD) that is characterized by aberrant bone mineralization and remodeling. ROD increases the risk of fracture and mortality in CKD patients. The underlying mechanisms of ROD remain elusive, partially due to the absence of an appropriate animal model. To address this gap, we established a stable mouse model of ROD using an optimized adenine-enriched diet and conducted exploratory analyses through ribonucleic acid sequencing (RNA-seq). Methods:. Eight-week-old male C57BL/6J mice were randomly allocated into three groups: control group (n = 5), adenine and high-phosphate (HP) diet group (n = 20), and the optimized adenine-containing diet group (n = 20) for 12 weeks. We assessed the skeletal characteristics of model mice through blood biochemistry, microcomputed tomography (micro-CT), and bone histomorphometry. RNA-seq was utilized to profile gene expression changes of ROD. We elucidated the functions of differentially expressed genes (DEGs) using gene ontology (GO) analysis, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis, and gene set enrichment analysis (GSEA). DEGs were validated via quantitative real-time polymerase chain reaction (qRT-PCR). Results:. By the fifth week, adenine followed by an HP diet induced rapid weight loss and high mortality rates in the mouse group, precluding further model development. Mice with optimized adenine diet-induced ROD displayed significant abnormalities in serum creatinine and blood urea nitrogen levels, accompanied by pronounced hyperparathyroidism and hyperphosphatemia. The femur bone mineral density (BMD) of the model mice was lower than that of control mice, with substantial bone loss and cortical porosity. ROD mice exhibited substantial bone turnover with an increase in osteoblast and osteoclast markers. Transcriptomic profiling revealed 1907 genes with upregulated expression and 723 genes with downregulated expression in the femurs of ROD mice relative to those of control mice. Pathway analyses indicated significant enrichment of upregulated genes in the sphingolipid metabolism pathway. The significant upregulation of alkaline ceramidase 1 (Acer1), alkaline ceramidase 2 (Acer2), prosaposin-like 1 (Psapl1), adenosine A1 receptor (Adora1), and sphingosine-1-phosphate receptor 5 (S1pr5) were successfully validated in mouse femurs by qRT-PCR. Conclusions:. Optimized adenine diet mouse model may be a valuable proxy for studying ROD. RNA-seq analysis revealed that the sphingolipid metabolism pathway is likely a key player in ROD pathogenesis, thereby providing new avenues for therapeutic intervention.